Case report: Epithelioid inflammatory myofibroblastic sarcoma treated with an ALK TKI ensartinib - Li, Mengmeng; Xing, Ruyue; Huang, Jiuyan; Shi, Chao; Wei, Chunhua; Wang, Huijuan (Frontiers in Oncology, 2023)
Epithelioid inflammatory myofibroblastic sarcoma (EIMS) is an aggressive variant of inflammatory myofibroblastic tumor (IMT) and has a poor prognosis. EIMS is characterized by epithelioid morphology, neutrophilic infiltrate and specific fusion partners of anaplastic lymphoma kinase (ALK). Despite no standard therapy for EIMS, ALK tyrosine kinase inhibitors (TKIs) are recommended for these tumors. The present case describes an abdominal mass that presented in a 31-year-old male. The patient suffered from recurrence and multiple metastases 2 months after surgery. Ensartinib was administered and RANBP2-ALK fusion was detected. A partial response has been observed for 4 months and there has been no recurrence. This study provided a successful case with sustained response of targeted therapy.